Religion and Post-Secular SDGs - Possamai, Adam (Jurnal Ilmu Sosial Indonesia (JISI), 2024)
Abstract. This article discusses theories of post-secularism, which is emerging in affinity with neoliberalism, and the participation of religions in achieving the UN Sustainable Development Goals (SDGs). The study used qualitative research methods with textual analysis approaches. The article argues that the current involvement of religion in achieving the SDGs is a result of religion's return as a recognised actor in the public sphere, as reflected in theories of post-secularism. Religion alone is not capable of achieving all the SDGs, but these SDGs will not be fully achieved without religion either. Indeed, religion is relevant to the SDGs (Schliesser 2023). While there are clear links between different theologies, such as Catholic (Cichos et al 2021) and Muslim (Khan and Haneef 2022), with the SDGs, there are also some points of contention. Keywords: Post-Secularism, Neo-Liberalism, SDGs, Religious Actors. Abstrak. Artikel ini membahas teori-teori post-sekularisme, yang muncul bersamaan dengan neoliberalisme, dan partisipasi agama-agama dalam mencapai Tujuan Pembangunan Berkelanjutan (SDGs) PBB. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan analisis tekstual. Artikel ini berargumen bahwa keterlibatan agama dalam pencapaian SDGs saat ini merupakan hasil dari kembalinya agama sebagai aktor yang diakui di ruang publik, seperti yang tercermin dalam teori-teori post-sekularisme. Agama saja tidak mampu mencapai semua SDGs, tetapi SDGs juga tidak akan sepenuhnya tercapai tanpa agama. Memang, agama relevan dengan SDGs (Schliesser 2023). Meskipun ada hubungan yang jelas antara teologi yang berbeda, seperti Katolik (Cichos et al. 2021) dan Muslim (Khan dan Haneef 2022), dengan SDG, ada juga beberapa poin yang diperdebatkan. Kata Kunci: Post-Sekularisme, Neoliberalisme, SDGs, Aktor Agama.